The First Charter of Virginia (1606) - (:unkn) unknown (My University, 1606)
Granted subjects all liberties, franchises, and immunities of free denizens. Also granted subjects the right to take, load, carry, transport armour, weapons, ordinances, muniiton, poweder, shott, victuals,and "all other things" necessary for the use and defense of the people.
Keywords: GUARANTEED RIGHT